1987
DOI: 10.1111/j.1600-0765.1987.tb02060.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of protease from culture supernatant of Bacteroides gingivalis

Abstract: Caseinolytic protease was isolated and purified, with high yield, from culture supernatant of Bacteroides gingivalis 381 by procedures including acetone fractionation, gel filtration on Sepharose CL‐6B, solubilization with 0.8% 1‐O‐N‐octyl‐β‐D‐glucopyranoside and affinity chromatography on arginine‐Sepharose 4B. By the affinity chromatography, the protease was separated into three isoenzymes, one of which was unadsorbed on the arginine‐Sepharose 4B, but the other two of which were adsorbed and eluted with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…Several proteinases with specificities similar to Arg-gingipain have been purified from various P. gingivalis strains (20,28,30,(47)(48)(49)(50)(51)(52). In this study, we found that all of the enzymatic activity for arginine-specific cysteine proteinase in P. gingivalis ATCC33277 might be derived from the rgpA and rgpB, as suggested by the total loss of the activity in the rgpA rgpB mutant.…”
Section: Discussionmentioning
confidence: 63%
“…Several proteinases with specificities similar to Arg-gingipain have been purified from various P. gingivalis strains (20,28,30,(47)(48)(49)(50)(51)(52). In this study, we found that all of the enzymatic activity for arginine-specific cysteine proteinase in P. gingivalis ATCC33277 might be derived from the rgpA and rgpB, as suggested by the total loss of the activity in the rgpA rgpB mutant.…”
Section: Discussionmentioning
confidence: 63%
“…Another consequence of the presence of B. gingivalis in saliva is the possible degradation of protective salivary proteins. Recently, it has been reported that B. gingivalis produces a protease which is capable of degradation and inactivation of salivary lysozyme (5). Therefore, the presence of B. gingivalis in the saliva may weaken the oral antibacterial properties.…”
Section: Discussionmentioning
confidence: 99%
“…Three peaks of activity against the two substrates and reactivity to specific antibodies were found. The Rgpspecific peak fractions were pooled, concentrated, and applied to an arginineSepharose column according to the protocol described by Otsuka et al (30), with modified elution volumes of 75 ml. The fractions were pooled and used for further analysis.…”
Section: Methodsmentioning
confidence: 99%